DNA demethylating agent 5-azacytidine inhibits myeloid-derived suppressor cells induced by tumor growth and cyclophosphamide treatment. Issue 5 (3rd January 2014) - Mikyšková, Romana; Indrová, Marie; Vlková, Veronika; Bieblová, Jana; Šímová, Jana; Paračková, Zuzana; Pajtasz-Piasecka, Elzbieta; Rossowska, Joanna; Reiniš, Milan
Abstract : Direct effects of DNA demethylating agent 5-azacytidine on immunosuppressive myeloid cell subsets in cancer, suggest that co-administration of 5AC could improve therapeutic efficacy of existing cancer therapy. ABSTRACT: MDSCs represent one of the key players mediating immunosuppression. These cells accumulate in the TME, lymphoid organs, and blood during tumor growth. Their mobilization was also reported after CY therapy. DNMTi 5AC has been intensively studied as an antitumor agent. In this study, we examined, using two different murine tumor models, the modulatory effects of 5AC on TU-MDSCs and CY-MDSCs tumor growth and CY therapy. Indeed, the percentage of MDSCs in the TME and spleens of 5AC-treated mice bearing TRAMP-C2 or TC-1/A9 tumors was found decreased. The changes in the MDSC percentage were accompanied by a decrease in the Arg-1 gene expression, both in the TME and spleens. CY treatment of the tumors resulted in additional MDSC accumulation in the TME and spleens. This accumulation was subsequently inhibited by 5AC treatment. A combination of CY with 5AC led to the highest tumor growth inhibition. Furthermore, in vitro cultivation of spleen MDSCs in the presence of 5AC reduced the percentage of MDSCs. This reduction was associated with an increased percentage of CD11c + and CD86 + /MHCII + cells. The observed modulatory effect on MDSCs correlated with a reduction of the Arg-1 gene expression, VEGF production, and loss of suppressive capacity. Similar, albeit weaker effects were observed when MDSCs from the spleens of tumor-bearing animals were cultivated with 5AC. Our findings indicate that beside the direct antitumor effect, 5AC can reduce the percentage of MDSCs accumulating in the TME and spleens during tumor growth and CY chemotherapy, which can be beneficial for the outcome of cancer therapy.